Synthesis and Characterization of High Molecular Weight Chitosan, and Antioxidant Activity of Its Chitosan Oligosaccharide Encapsulation - Adhikari, Hari Sharan; Garai, Aditya; Marasini, Bishnu Prasad; Adhikari, Rameshwar; Yadav, Paras Nath (Journal of Nepal Chemical Society, 2021)
High molecular weight nanocrystalline chitosan (HMWNC)with Mw of 350 kDa and 66.92% DDA was prepared by alkaline N-deacetylation of chitin that was abundantly obtained after demineralization and deproteinization of pulverized crab shells, and commercially available chitosan oligosaccharide (COS) with average Mw< 3000 Da and 87% DDA was encapsulated with HMWNC. The encapsulation of COS as a pharmaceutical ingredient into HMWC was hypothesized to enhance the bioavailability of COS in target cells. The HMWNC encapsulated chitosan oligosaccharide (COS-HMWNC) showed in vitro antioxidant activity on 1,1-diphenyl-2-picrylhydrazyl (DPPH) radicals (IC50 = 512.6±14.4 μg/mL) while others showed less than 50% inhibition at 1000 μg/mL. The lower the molecular weight of chitosan, the higher was the antioxidant activity. The study showed that the encapsulation of COS molecules in HMWNCcould be used as a simple and effective way of enhancing the antioxidant activity of COS.